Design and Cost-Effectiveness of 5-Tier Foldable Container - Yi, Jiwoon; Park, Jang Ho; Park, Wonsuk; Choo, Jinkyo F. (Arabian Journal for Science and Engineering, 2022)
Foldable containers are considered an effective solution to deal with the endemic imbalance in the repositioning of empty containers. Several foldable containers were commercialized without clear breakthrough in the market and most current researches are still limited to small pilot projects. This paper presents the design of a new 5-tier stacking foldable container with convenient folding and unfolding process and that can be produced economically compared to previous products. The selected size of the container is the standard 40-ft high cube because it represents about 70% of the maritime container fleet transiting Korean ports. The presented foldable container passed the tests for international certifications ISO 1496-1 and CSC required for its application on site. Differently from the 4:1 folding ratio adopted by most previous products, a ratio of 5:1 is chosen to further the economy in storage space. In addition, cost analysis is also implemented for both transborder and transcontinental shipments to demonstrate the economic viability of the proposed foldable container.
Keywords: 40-ft high-cube container; Cost-effectiveness; Empty container repositioning; Foldable container; Folding ratio